A sustained intravitreal drug delivery system with remote real time monitoring capability. (15th September 2015) - Hou, Huiyuan; Nieto, Alejandra; Belghith, Akram; Nan, Kaihui; Li, Yangyang; Freeman, William R.; Sailor, Michael J.; Cheng, Lingyun
Graphical abstract: Abstract: Many chorioretinal diseases are chronic and need sustained drug delivery systems to keep therapeutic drug level at the disease site. Many intravitreal drug delivery systems under developing do not have mechanism incorporated for a non-invasive monitoring of drug release. The current study prepared rugate porous silicon (pSi) particles by electrochemical etching with the current frequency ( K value) of 2.17 and 2.45. Two model drugs (rapamycin and dexamethasone) and two drug-loading strategies were tested for the feasibility to monitor drug release from the pSi particles through a color fundus camera. The pSi particles ( k = 2.45) with infiltration loading of rapamycin demonstrated progressively more violet color reflection which was negatively associated with the rapamycin released into the vitreous ( r = −0.4, p < 0.001, pairwise). In contrast, pSi with K value of 2.17 demonstrated progressive color change toward green and a weak association between rapamycin released into vitreous and green color abundance was identified ( r = −0.23, p = 0.002, pairwise). Dexamethasone was covalently loaded on to the fully oxidized pSi particles that appeared in vitreous as yellow color and fading over time. The yellow color decrease over time was strongly associated with the dexamethasone detected from the vitreous samples ( r = 0.7, p < 0.0001, pairwise). These results suggest that engineered porous silicon particles may be used as a self-reporting drug delivery system for a non-invasive real time remote monitoring. Statement of Significance: The current study, for the first time, demonstrated proof of concept that engineered porous silicon photonic crystal may deliver therapeutics in a controlled fashion while at the same time might offer a noninvasive remote monitoring of its payload release in a living eye. Porous silicon photonic crystal changes color which is in association with its payload release into vitreous. With further optimization, the color change may be harnessed to inform eye care professionals of real time drug concentration in the eye and allow them to make informed decision to re-dose the patients.